Pengaruh Stres Kerja dan Lingkungan Kerja Fisik terhadap Kinerja Karyawan pada Klinik Abdul Karim Medika Center - Eka Sulistiowati; Asep Jamaludin; Zenita Apriani (Lembaga Pengembangan Kinerja Dosen, 2026)
The objective of this study is to analyze the impact of work-related stress and the physical work environent on employeee perfornance at the Abdul Karim Medika Center Clinic. The reseearch method employed a quantittative aproach using a causal-associiative study design. The population consisted of 52 employees, while the selected sample conprised 46 employees chosen through simple random sampling. Data were collected through questionnaires, observations, and docunentation. It was found that work-related stress had a negative and significant impact on employee performance (R² = -0.340 and Sig. = 0.002 < 0.05). Meanwhile, the physical work environnent had a positive and significant impact on employee performance (R² = 0.528 and Sig. = 0.000 < 0.05). Concurrently, work stress and the physical work environment had a significant impact on employee perfornance (F calculated 30.621 and Sig. 0.000 < 0.05). The results of the coefficient of determination revealed that 68% of the variation in employee performance was explained by work stress and the physical work environment, while the remaining 32% was attributed to other factors.